Developing reconciled quarterly distributional national wealth: Insight into inequality and wealth structures - Janina Engel; Pau Gayà Riera; Joseph Grilli; Pierre Sola (European Central Bank (ECB), 2022)
Distributional accounts for households enable measurement, study developments and identify drivers of inequality. Distributional information on households' wealth is available from the Household Finance and Consumption Survey only for three points in time (2009 - 2018), while aggregates are available quarterly. This paper presents a novel methodology for deriving quarterly distributional national wealth by (i) improving the alignment of survey fieldwork periods with the national accounts' dates; (ii) correcting for differences in several concepts; (iii) estimating missing wealthy households; (iv) developing time series; and (v) computing euro area aggregates. This paper finds an increase in the net wealth Gini of most euro area countries since 2009; that the richest 1% holds 28% of total net wealth, while the bottom 50% holds 4%; and that the net wealth of the top 1% has grown by almost 50%, compared to 28% for the remaining 99%, with a decrease in the bottom 20%.
Keywords: C46; D31; E27; G51; N34; 330; Wealth inequality; HFCS; National Accounts; Pareto distribution